Effect of Ochratoxin-A on Mouse Embryos (Baghdad Science Journal, 2018)
This study sought to determine malformation caused by Ochratoxin-A (OTA) on mouse embryos. Twenty adult female white Swiss mice (mus msculus) were divided into four groups, with five females per group, and with one male placed with two females in a cage. Avaginal plug was observed in the early morning and the day of mating was considered as day of pregnancy followed by the first day of pregnancy. Three sub lethal concentrations of OTA were applied to the respective groups (other than the control), 1mg/kg, 2mg/kg and 4mg/kg. The animals were given 0.1 ml per 10 gm body weight per concentration of OTA once a day during days 7-14 of pregnancy. The control group animals were given distilled water. The pregnant mice were dissected, and the embryos were extracted in order to identify the effects of the OTA. Number of parameters were studied including, difference in body weight of the mice before mating and after the end of the experiment, the weights and lengths of embryo, as well as a study of embryo malformation. The study shows no significant differences in the mean body weight of the pregnant mice in the 1 mg/kg group, compared to control group. A significant (P